Eficácia de curso via telemedicina sobre questões sexuais no Ciclo Gravídico Puerperal para o médico residente de Ginecologia e Obstetrícia - Vieira, Teresa Cristina Souza Barroso [UNIFESP] (2016)
Introduction: There are few sexual education programs specifically targeted at medical residents. Objective: To evaluate the efficaciousness of an online course related to the knowledge of residents about sexual issues during pregnancy. Methods: Longitudinal study conducted between April and September 2014 involving 219 medical residents from five hospitals in São Paulo city. The course lasted a total of 24 hours, divided in 10 online classes and discussion chats. Before and after the course, the participants answered tests to evaluate their knowledge about the topic. After the course, they also answered a questionnaire to evaluate their educational experience. Student?s t test was used to analyze the initial and final test scores; p values <0.05 were considered statistically significant. Results: A total of 143 residents concluded the course, most of whom were 2nd or 3rd year residents. Most participants reported that they did not have any sexology classes as undergraduates or in their residency and that they lacked specific knowledge in this area to manage their patients. The mean test scores increased significantly at the end of the course: 4,4 (±1,6) to 6,0 (±1,3) (out of maximum score of 10), before and after the course, respectively (p<0,0001). Most of the participants (93%) rated the overall quality of the course as higher than expected. Conclusions: The online course about sexuality during pregnancy led Obstetrics and Gynecology Residents to significantly increase their knowledge on this topic. This type of initiative could be useful to improve the education of future specialists in Obstetrics and Gynecology.